Developing a conceptual model of virtual organisations for citizen science. (15th September 2010) - Wiggins, Andrea; Crowston, Kevin
This paper develops an organisation design-oriented conceptual model of scientific knowledge production through citizen science virtual organisations. Citizen science is a form of organisation design for collaborative scientific research involving scientists and volunteers, for which internet-based modes of participation enable massive virtual collaboration by thousands of members of the public. The conceptual model provides an example of a theory development process and discusses its application to an exploratory study. The paper contributes a multi-level process model for organising investigation into the impact of design on this form of scientific knowledge production.